Beta diversity of aquatic insects (Ephemeroptera, Plecoptera and Trichoptera) across stream microhabitats - Jhenifer Simões dos Santos; Rogério Campos de Oliveira; Tácio Duarte; Cleto Kaveski Peres (Acta Limnologica Brasiliensia, 2025)
Abstract: Aim We evaluated how the combination of environmental characteristics affects the beta diversity of the EPT (Ephemeroptera, Plecoptera and Trichoptera) community across stream microhabitats. Methods The samples were collected in 12 streams around the Itaipu Reservoir (Paraná, Brazil). We sampled four types of substrates in triplicate with the aid of a Surber sampler. The samples were classified into CSD (sand and clay) and STO (gravel, pebbles, and boulders). The composite substrate of leaf packs (leaves and twigs) was divided into RLP (rapid leaf packs) and BLP (backwater leaf packs). Results We recorded a significant change in EPT composition among the microhabitats evaluated and different genera associated with each substrate category. However, beta diversity did not significantly differ among microhabitats. Thus, we found the highest beta diversity value in the CSD (sand and clay) category and the greatest contribution of the turnover component. Conclusions The partitioning of beta diversity into its components helped understand ecological patterns at local scales, highlighting the importance of microhabitat diversity in stream systems for maintaining the structure and composition of aquatic fauna.